Integrability on the Abstract Wiener Space of Double Sequences and Fernique Theorem - Jeong-Gyoo Kim (Journal of Function Spaces)
The integrability of a function defined on the abstract Wiener space of double Fourier coefficients is explored. The abstract Wiener space is also a Hilbert space. We define an orthonormal system of the Hilbert space to establish a measure and integration on the abstract Wiener space. We examine the integrability of a function eα·2 defined on the abstract Wiener space for Fernique theorem. With respect to the abstract Wiener measure, the integral of the function turns out to be convergent for α<1/2. The result provides a wider choice of the constant α than that of Fernique.